The Relationship of Distributive Justice and Procedural Justice on Organizational Commitment: An Empirical Testing - Ghimire, Binod (Tribhuvan University Journal, 2017)
This paper investigates the relationship between organizational justice and organizational commitment among the employees of different organizations from Kathmandu Valley. This research study analyzes the impact of organizational justice as encompassed by two components, namely distributive justice and procedural justice on employee’s commitment. This study is descriptive and analytical. The sample consists of managerial and non-managerial employees who have volunteered to participate in the study. This study reveals a positive and significant relationship showing that the foundation of an employee’s commitment is within the application of both distributive and procedural justice, with procedural justice having stronger effect. The findings in this study would offer insight to the managers and business organization in Nepal to formulate strategies that involve in work factors such as distributive and procedural justice for the improvement of the human resource development.